Surgical excision of perineal nodular induration: A cyclist’s third testicle - Awad, Mohannad A.; Murphy, Gregory P.; Gaither, Thomas W.; Osterberg, E. Charles; Sanford, Thomas A.; Horvai, Andrew E.; Breyer, Benjamin N. (Canadian Urological Association Journal, 2017)
Perineal nodular induration (PNI), or biker’s nodule, is a rare, bothersome, pseudotumour. Herein, we describe the surgical technique used to treat a healthy cyclist who developed an enlarging PNI for five years that grew into a perineal mass. The mass prevented him from cycling due to worsening discomfort and heaviness. The PNI-associated mass was successfully removed by wide surgical excision and a local advancement flap. Subsequently, the patient resumed cycling. Histopathology report demonstrated a benign lesion with abundant ropy collagen with native smooth muscle, vessels, and rare fibroblast-like spindle cells. With the increasing popularity of cycling, PNI may become more common, and health providers should be aware of this rare entity and how it can be safely removed.